Primary malignant melanoma of small intestine – A rare case report - Palak Patel; Prashant Parikh; Bhavna Mehta; Rahul Yadav; Rutvik Raval; Sandip Shah; Mandava Rao (Eastern Journal of Medical Sciences, 2020)
Primary malignant melanoma of the intestine is an extremely rare lesion that may arise from large bowel. Hereby, we report a case of a 35-year-old female who presented with abdominal pain of 1 month duration. On positron emission tomography-computed tomography, a hypermetabolic mass observed in the pelvic ileal loop with no lesions elsewhere in the body. The surgically excised specimen was diagnosed as primary small intestinal melanoma by histopathological examination, which was further confirmed by the presence of melanoma markers, that is, Melan-A, HMB45, and S100 protein.